Influence of temperature on the subcritical water extraction of Actinidia arguta leaves: A screening of pro-healthy compounds - Silva, Ana Margarida (2022)
Actinidia arguta is a species disseminated in Europe and classified by the Chinese Herbal Medicine as a medicinal plant. The fruit (kiwiberry) has been extensively exploited for multiple purposes, while leaves where discarded. The objective of this study was to evaluate the optimal Subcritical Water Extraction (SWE) temperature (110 °C - 160 °C) of antioxidants and polyphenols from A. arguta leaves. The optimal temperature of extraction was 123 °C, revealing the highest phenolic and flavonoid contents and good scavenging efficiencies against HOCl (IC50 = 17.06 μg/mL) and O2●- (IC50 = 335.2 μg/mL), without toxicity on intestinal cells. The phenolic profile was characterized by high amounts of phenolic acids (e.g., gallic acids), flavanols (catechin) and flavonols (e.g., quercetin-3-O-galactoside). This work allows to conclude that SWE can be a useful extraction technique for the recovery of polyphenolics from A. arguta leaves.